Teachers’ experiences and representations on evaluation and assessment in initial training. Reflections and considerations for University Teaching - Montalbetti, Katia (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2015)
Nowadays the theme of evaluation and assessment has crucially been at the heart of considerable debate and attention referring to the quality of educational and formative systems. Know how to evaluate and how to do it in a well manner is a complex task for teachers due to also the increasing requests. This essay focuses upon an exploratory research conducted with students involved in university initial training to become teachers. It aims to reconstruct the previous evaluation experience lived at school and to investigate representations about the idea of evaluation and assessment. It is assumed that these elements could influence the approach to evaluation by the future teachers. Considering what has highlighted up to this point, acquire information is essential to set efficacious university courses related to evaluation issues and to foster learning, useful for professional development.